The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1080/00028487.2014.911206
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tolerance, Survival, and Recruitment of Cyprinids Exposed to Competition and Chronic Heat Stress in Experimental Streams

Abstract: We examined survival, competition, and recruitment among cyprinids that were subjected to interspecific and intraspecific competition and chronic heat stress in large, outdoor experimental streams. The study was conducted in 2011 during the hottest summer (also one of the driest summers) recorded in Texas. We measured survival of Red Shiners Cyprinella lutrensis, Blacktail Shiners Cyprinella venusta, and Central Stonerollers Campostoma anomalum stocked at varying densities to examine competitive interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Grossman et al (2006) found that densitydependence models were the best predictors of abundance of insectivorous Mottled Sculpin Cottus bairdii. Dekar et al (2014) used stream mesocosms to evaluate intraspecific competition in omnivorous Blacktail Shiner Cyprinella venusta stocked at varying densities and found that an increase in diet breadth to include lower quality resources occurred in higher density treatments. While these two studies indicate density dependence is possible in nonsalmonid stream fish, it is not clear the degree to which this occurs in fishes from other tropic guilds and the impacts it may have on population regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Grossman et al (2006) found that densitydependence models were the best predictors of abundance of insectivorous Mottled Sculpin Cottus bairdii. Dekar et al (2014) used stream mesocosms to evaluate intraspecific competition in omnivorous Blacktail Shiner Cyprinella venusta stocked at varying densities and found that an increase in diet breadth to include lower quality resources occurred in higher density treatments. While these two studies indicate density dependence is possible in nonsalmonid stream fish, it is not clear the degree to which this occurs in fishes from other tropic guilds and the impacts it may have on population regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The red shiner is an invasive species that has rapidly expanded its range throughout North America (Mapping the potential distribution of the invasive Red Shiner, Cyprinella lutrensis (Teleostei: Cyprinidae) across waterways of the conterminous United States). Red shiners thrive in waters varying widely in available light spectra, with mean of yearly median habitat turbidity measures ranging from 10 to 140 nephelometric turbidity units (NTU) and withstand temperatures ranging from 0°C-37°C (Dekar et al, 2014; Dugas and Franssen, 2012; Matthews, 1986; Matthews and Hill, 1977). Visual signaling is an important part of the biology of red shiners, with males displaying elaborate nuptial coloration (Dugas and Franssen, 2011).…”
Section: Introductionmentioning
confidence: 99%